(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The artistic work in the works of satellite stations, Arab or international, depends on the generating of meanings in the television performance visually through semantic and expressive representations based on the elements of visual formation, This is done through the thematic vision on which the structural fabric and architecture of the text depends, within symbols, icons, and expressive semantics based on a set of theorizing references. It is mainly formed according to the aesthetic representation and intellectual construction depending on the language of the mediator through the thematic employment in the use of the elements of the pictorial language based on the inclusion of narrative structures and their engagements in the visual production and their inclusion of generative meanings that impose requirements for the production of meanings in satellite channels, As there is a label and affiliation in drawing imagination and creativity with what the spectator watches, and the researcher has formulated the title of her research according to the following: Diversity Thematic of the structure for the visual formation in satellite channels.